Problems Related to the Learning of English Pronunciation at the First Year Students of English Department Universitas Muhammadiyah Makassar - Haris, Kurnia; Saiful; AM, St. Asmayanti (FKIP Unismuh Makassar, 2023)
This research aimed to investigate the problems of pronouncing diphthongs and to reveal the factors causing the problems of pronouncing diphthongs at the First Year Students of English Department Universitas Muhammadiyah Makassar. The researcher used Descriptive qualitative research in this researh. The researcher used document analysis and inteview as intruments in data collection. The researcher took 10 students from the second semester of English Department as sample in this research.The findings of this research showed that there were two problems faced by the students of pronouncing diphthongs, including the students monophthongized the diphthong sounds to pure vowel sounds and substituted one diphthong sounds with other diphthong sounds. Meanwhile, the factors that cause the students problems of pronouncing diphthong sounds are the influence of mother tongue, lack of knowledge in diphthong materials, lack of practice, difficult to memorize diphthong sounds, fossilization, and lack of motivation.